METHODS OF ANALYSIS OF INTANGIBLE ASSETS OF ENTERPRISES (INNOVATIVE ECONOMY, 2021)
Yasyshena V.V., Pyliavets V.M. METHODS OF ANALYSIS OF INTANGIBLE ASSETS OF ENTERPRISESPurpose. The aim of the article is the isolation, systematization and improvement of methodological approaches that must be taken into account when analysing the intangible assets of enterprises.Methodology of research. The theoretical basis of the study is the scientific works of domestic and foreign scientists on the problems of research in the analysis of intangible assets. The methodological basis of the study are general scientific methods (abstraction, comparison, generalization, grouping, systematization, analysis, synthesis), which are used in the analysis of intangible assets; graphical method – for a visual representation of intangible assets, calculated on the basis of financial statements of enterprises; abstract and logical method – to formulate research conclusions.Findings. The successive stages of the methodology of analysis of intangible assets are identified through the definition of the following indicators: value dynamics; the share of intangible assets in the property of the enterprise; suitability; movement; efficiency of use; general trends in efficiency. The obtained results of the method of analysis of intangible assets on the basis of approbation according to the financial statements of food industry enterprises in Vinnytsia region are revealed.It is substantiated and proposed to take into account the main requirements in determining the effectiveness of the use of intangible assets, namely: indicators of the volume of intangible assets in the financial statements are objective; with a sufficient share of intangible assets in the property of the enterprise during the period, their level increases; indicators of suitability, compensation, growth, profitability and turnover and their dynamics are positive. The general trend of efficiency of use of intangible assets, the ratio of the growth rate of intangible assets is maintained to establish at a lower level than the growth rate of revenue from sales of goods, products, works, services and profit.Originality. The requirements that must be taken into account when conducting an analysis of the effectiveness of the use of intangible assets, which, in contrast to the existing approach, are established and substantiated allows you to take into account a number of factors that affect the objective determination of the effectiveness of the use of intangible assets and to approach the analysis objectively.Practical value. The implementation of the recommendations proposed in the publication to improve the methodology of analysis of intangible assets will help increase the efficiency of their use and management. The results of the study have found practical application in the food industry of Ukraine.Key words: intangible assets, analysis, accounting, financial reporting, dynamics, efficiency, food industry.
Keywords: Key words; intangible assets; analysis; accounting; financial reporting; dynamics; efficiency; food industry.